Multi-Level Factors and Burnout : The Mediating Role of Perception on Teacher Performance Assessment (TPA) - Audy, Audy; Desfitranita (Relevance: Journal of Management and Business, 2025)
Teacher performance and burnout are critical to maintaining educational quality, and they are often affected by psychological and social factors. This study examines the impact of self-esteem, team cohesiveness, and psychological safety climate on employee performance and burnout, with the perception of Teacher Performance Assessment (TPA) as a mediating factor. A quantitative approach was employed, surveying 201 public high school teachers in Bogor Regency, West Java, Indonesia. Data were analysed using Structural Equation Modelling (SEM-PLS) to explore direct and indirect relationships between variables. The findings indicate that team cohesiveness and psychological safety climate significantly enhance the perception of TPA, improving employee performance and reducing burnout. Additionally, self-esteem has a direct positive effect on performance. However, no significant relationship was found between self-esteem and perception of TPA, nor between psychological safety climate and burnout, suggesting the presence of contextual moderating factors. This study contributes to the understanding of multi-level factors affecting teacher performance and burnout, emphasising the importance of fostering a supportive work environment. Practical implications include recommendations for educational institutions to strengthen team collaboration, enhance psychological security, and ensure fair and transparent performance assessments to improve teacher effectiveness and overall educational quality.